Semiotic Study of Japanese Views on Sea in Hayao Miyazaki’s Ponyo on the Cliff by the Sea - Noviana Fajria (E3S Web of Conferences, 2020)
This paper is a semiotic study of Hayao Miyazaki’s anime Ponyo on the Cliff by the Sea. The purpose of thi s study is t o reveal the Japanese views on sea in the anime. This anime was selected because it is considered to represents the modern Japanese narrative related to the sea, and regarding that anime as a popular literary work is generally more acceptable at various age levels of audience than classical literary works. The results of semiotic reading on this anime are five Japanese views on sea, which are 1) sea as a source of life; 2) sea as a source of prosperity; 3) sea as a source of strength or energy; 4) sea as a source of beliefs; and 5) sea as a source of beauty.